Socioeconomic Traces of Nutmeg Farmers in Liliboi: Between Tradition and Modern Challenges - Jeter Donald Siwalette (Khazanah Sosial, 2025)
This study aims to assess the socio-economic conditions and management systems of nutmeg cultivation in Liliboi Village, West Leihitu District, Central Maluku Regency. Nutmeg is an important commodity in Ambon Island, and most villagers depend on this crop for their livelihoods. This study used a qualitative descriptive method, involving 30 nutmeg farmers who were randomly selected as respondents. Primary data were collected through direct interviews, while secondary data were obtained from relevant official references. Data were analyzed using score distribution and assessment scale categories. The findings indicate that the socio-economic conditions in Liliboi Village are quite adequate. The nutmeg cultivation management system is still traditional and hereditary. The change from collective land ownership to individual ownership has an impact on farmers' production and income. This study concludes that although the socio-economic conditions of nutmeg farmers in Liliboi Village are relatively good, they still rely on traditional methods. Changes in land ownership structures affect the way nutmeg is managed and encourage diversification of agricultural activities, which contributes to farmers' income.